2018
DOI: 10.1177/0218492318760692
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between epicardial fat thickness and aortic valve sclerosis

Abstract: Background Epicardial fat is a true visceral fat deposit with adverse effects through the secretion of numerous proinflammatory and proatherogenic cytokines. Previous studies showed an association between aortic valve sclerosis and coronary artery disease. The aim of this study was to determine the correlation between epicardial fat thickness and aortic valve sclerosis. Method The study involved 225 patients who were admitted for coronary angiography due to new-onset angina. They underwent transthoracic echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Parisi et al found an increased EFT thickness in patients referred for surgical aortic valve replacement due to high-grade AS compared with matched controls without AS [29]. Furthermore, greater EFT thickness significantly correlated with elevated serum levels of the pro-inflammatory cytokines IL-6, TNF-α, IL-1β, and MCP-1 [30]. In our study, there was no positive correlation between EFT and the Agatston score of the aortic valve.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Parisi et al found an increased EFT thickness in patients referred for surgical aortic valve replacement due to high-grade AS compared with matched controls without AS [29]. Furthermore, greater EFT thickness significantly correlated with elevated serum levels of the pro-inflammatory cytokines IL-6, TNF-α, IL-1β, and MCP-1 [30]. In our study, there was no positive correlation between EFT and the Agatston score of the aortic valve.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study, there was no positive correlation between EFT and the Agatston score of the aortic valve. This would appear to contradict the findings of other studies: in 225 patients undergoing coronary angiography due to new-onset angina, Nabati et al found higher amounts of aortic valve sclerosis expressed via an aortic valve sclerosis score index in patients with an echocardiographic EFT thickness ≥ 7 mm [30]. In addition, Mahabadi et al observed a greater EFT thickness measured via echocardiography in patients with severe AS compared with patients without AS [31].…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, epicardial and visceral adipose tissue were positively associated with atherosclerotic burden, whereas subcutaneous adipose tissue had a negative association (85). Epicardial adipose tissue was also associated with vascular inflammation and arterial stiffness (86), aortic valve sclerosis score (87), LV hypertrophy and cardiomyocyte fibrosis/ apoptosis, (88), and obstructive sleep apnea (89). Epicardial adipose tissue secretes more phospholipase A2 II with ischemia, resulting in more phospholipid hydrolysis and generation of local FFA (90).…”
Section: Metabolic Drivers Adiposity-based Chronic Diseasementioning
confidence: 99%
“…Transthoracic echocardiography was performed to assess both EAT thickness and the average aortic valve sclerosis score index. The authors reported that patients with an EAT thickness ≥7 mm were older, with more frequent hypertension and hyperlipidemia, and showed greater LV hypertrophy and a higher average aortic valve sclerosis score index, thus suggesting an association between EAT and aortic leaflets calcification already in the early stages of the disease ( 99 ).…”
Section: Eat and Aortic Stenosismentioning
confidence: 99%